Persistent Chlamydia trachomatis, Neisseria gonorrhoeae or Trichomonas vaginalis positivity after treatment among human immunodeficiency virus-infected pregnant women, South Africa. (March 2020) - Medina-Marino, Andrew; Mudau, Maanda; Kojima, Noah; Peters, Remco PH; Feucht, Ute D; Vos, Lindsey De; Olivier, Dawie; Muzny, Christina A; McIntyre, James A; Klausner, Jeffrey D
The objective of this study is to assess the predictors and frequency of persistent sexually transmitted infection (STI) positivity in human immunodeficiency virus (HIV)-infected pregnant women treated for Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG) or Trichomonas vaginalis (TV) infection. We enrolled HIV-infected pregnant women attending their first antenatal care visit and tested them for urogenital CT, NG and TV infection using Xpert® CT/NG and TV assays (Cepheid, Sunnyvale, CA). Those testing positive were treated. Participants either notified partners to seek treatment or were given extra medication to deliver to partners for treatment. Repeat testing was conducted approximately 21 days post-treatment or treatment initiation. Among 427 participants, 172 (40.3%) tested positive for any STI. Of the 136 (79.1%) that returned for repeat testing, 36 (26.5%) tested positive for the same organism: CT = 27 (26.5%), NG = 1 (6.3%), TV = 11 (16.7%). Persistent CT positivity was independently associated with having more than one sex partner in the preceding 12 months (adjusted-prevalence ratio [aPR] = 3.03, 95% CI: 1.44–6.37) and being newly diagnosed with HIV infection during the first antenatal care visit compared to those currently on antiretroviral therapy (aPR = 3.97, 95% CI: 1.09–14.43). Persistent TV positivity was associated with not knowing if a partner sought treatment following STI disclosure (aPR = 12.6, 95% CI: 2.16–73.5) and prior diagnosis of HIV but not currently on antiretroviral therapy. (aPR = 4.14; 95% CI: 1.25–13.79). We identified a high proportion of HIV-infected pregnant women with persistent CT or TV positivity after treatment. To decrease the risk of re-infection, enhanced strategies for partner treatment programmes are needed to improve the effectiveness of STI screening and treatment in pregnancy. The relationship between not being on antiretroviral therapy and persistent STI positivity needs further study.